Pemberdayaan dan Kerjasama Ekspor Petani Agave dan Sansevieria Melalui CV Botani Flora Indonesia - Rinda Eka Aprilia Adzanis; Dewi Rahmawati; Dita Atasa (Lembaga Pengembangan Kinerja Dosen, 2024)
Empowerment and export cooperation of agave and sansevieria farmers through CV Botani Flora Indonesia aims to determine the value of exports, the main purpose of exports, the obstacles faced, and strategies for increasing agave and sansevieria exports from Indonesia. The data collection methods used were interviews, observation and documentation. The results show that the collaboration between CV Botani Flora Indonesia and Agave and Sansevieria farmers has increased their export results.